2019
DOI: 10.1186/s40575-019-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

DLA class II risk haplotypes for autoimmune diseases in the bearded collie offer insight to autoimmunity signatures across dog breeds

Abstract: BackgroundPrimary hypoadrenocorticism (Addison’s disease, AD) and symmetrical lupoid onychodystrophy (SLO) are two clinical conditions with an autoimmune etiology that occur in multiple dog breeds. In man, autoimmunity is associated with polymorphisms in immune-related genes that result in a reduced threshold for, or defective regulation of, T cell activation. The major histocompatibility complex (MHC) class II genes encode molecules that participate in these functions, and polymorphisms within these genes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…However, because it was only identified in only 2% of controls and the 95% CI is very wide (0–0.95), this association should be interpreted with caution and further investigated in a larger cohort of WHWTs. A similar observation was made by a study of DLA class II haplotypes in AD [ 42 ]: the same haplotype (001:01--001:01--036:01) was identified solely in the control population of WHWTs (0 cases; 6 controls). However, this may be due to the WHWT control population being much larger than the case population in that study (43 cases; 166 controls).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, because it was only identified in only 2% of controls and the 95% CI is very wide (0–0.95), this association should be interpreted with caution and further investigated in a larger cohort of WHWTs. A similar observation was made by a study of DLA class II haplotypes in AD [ 42 ]: the same haplotype (001:01--001:01--036:01) was identified solely in the control population of WHWTs (0 cases; 6 controls). However, this may be due to the WHWT control population being much larger than the case population in that study (43 cases; 166 controls).…”
Section: Discussionsupporting
confidence: 80%
“…In this breed, DLA haplotype 1 (001:01--001:01--002:01) was found to be associated with increased risk of DM (OR = 1.59, 95% CI = 1.02–2.47), which suggests that this particular DLA-type might play a role in the pathogenesis of beta cell loss/dysfunction in this breed. This DLA haplotype has previously been associated with increased risk of hypothyroidism in Gordon Setters [ 41 ] as well as primary hypoadrenocorticism (Addison’s disease; AD) in WHWT and Leonberger breeds [ 42 ]. Notably, both hypothyroidism associated with lymphocytic thyroiditis and primary hypoadrenocorticism are considered to have an autoimmune basis and demonstrate breed differences in susceptibility [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dogs, genetic susceptibility to hypoadrenocorticism has been evidenced through breed predispositions and further revealed by pedigree analyses [21][22][23][24][25][26]. More focussed dissection of underlying genetic factors has shown dog leukocyte antigen (DLA) class II variation to be significantly associated with hypoadrenocorticism [5,[27][28][29]. Whilst the significance of these findings have been contested [30,31] it is the case that fine mapping techniques have confirmed MHC associations in human studies as well as revealing further associations and the importance of epistasis [32].…”
Section: Introductionmentioning
confidence: 99%
“…A genome-wide association study (GWAS) subsequently identified a region of association on canine chromosome (CFA) 12 (12:555,475-3,775,420) that includes the DLA class II genes in English and Gordon Setters [4]. Recently, a study by our laboratory has confirmed the association of two dog leukocyte antigen (DLA) class II risk haplotypes with SLO in the Bearded Collie [12]. Combined, these findings support an autoimmune etiology for SLO.…”
Section: Introductionmentioning
confidence: 99%